Some Coincidence and Common Fixed Point Results in Fuzzy Metric Space with an Application to Differential Equations. (29th October 2021) - Rehman, Saif Ur; Shamas, Iqra; Jan, Naeem; Gumaei, Abdu; Al-Rakhami, Mabrook
Abstract : In this paper, we study some coincidence point and common fixed point theorems in fuzzy metric spaces by using three-self-mappings. We prove the uniqueness of some coincidence point and common fixed point results by using the weak compatibility of three-self-mappings. In support of our results, we present some illustrative examples for the validation of our work. Our results extend and improve many results given in the literature. In addition, we present an application of fuzzy differential equations to support our work.